Lichenoid Drug Eruption Secondary to Growth Hormone in a Case of Noonan’s Syndrome - Uffra Shaikh; Swagata Tambe; Kirti Jangid; Prashant Patil (Indian Journal of Paediatric Dermatology, 2025)
Lichenoid drug reactions (LDRs) are a type of cutaneous adverse drug reaction that clinically resembles lichen planus and demonstrates lichenoid tissue reaction on histopathology. These have been implicated by various topical, oral, and injectable medications. Noonan’s syndrome (NS) is an autosomal dominant disorder with skeletal deformity, particularly short stature as a common feature for which growth hormone (GH) therapy is effective. Here, we present a 16-year-old male with NS who developed lichenoid dermatitis on initiation of injectable GH therapy and showed remission with oral apremilast and after withdrawal of the injectable GH therapy.